2017
DOI: 10.29252/ijrm.15.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole+ GnRH antagonist stimulation protocol in poor ovarian responders undergoing intracytoplasmic sperm injection cycles: An RCT

Abstract: Background:Gonadotropin-releasing hormone (GnRH) antagonist protocol has been proposed as a potentially proper option for the patients with limited ovarian reserve. Nevertheless, there is no significant difference in terms of clinical pregnancy between the GnRH antagonist and agonist cycles. The use of aromatase inhibitors such as letrozole was suggested by some studies. Objective:The object of this study was to evaluate the efficacy of letrozole co-treatment with GnRH-antagonist protocol in ovarian stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Mitri et al be significantly improved by the supplementation of poor responders with letrozole (Goswami et al 2004, Schoolcraft et al 2008, Yarali et al 2009, Jovanovic et al 2011, Mohsen & El Din 2013, Ebrahimi et al 2017. Furthermore, analysis of pooled data from several studies also fail to show a significant association with increased clinical pregnancy rates (Bosdou et al 2012, Jeve & Bhandari 2016, Kamath et al 2017.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…Mitri et al be significantly improved by the supplementation of poor responders with letrozole (Goswami et al 2004, Schoolcraft et al 2008, Yarali et al 2009, Jovanovic et al 2011, Mohsen & El Din 2013, Ebrahimi et al 2017. Furthermore, analysis of pooled data from several studies also fail to show a significant association with increased clinical pregnancy rates (Bosdou et al 2012, Jeve & Bhandari 2016, Kamath et al 2017.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…The risk of bias was assessed as high, low or unclear/unreported in seven categories (random sequence generation, allocation concealment, blinding of participants, blinding of outcome assessments, incomplete outcome data, selective reporting and other biases). Only five studies were judged to be free of bias in all of the categories [24,25,41,55,65]. Bias was mostly reported for allocation concealment, blinding of participants and blinding of outcome assessment (Fig.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Co-administration of 2.5 mg letrozole for the first 5 days of ovarian stimulation during a high dose FSH/hMG GnRH-antagonist protocol, resulted in a higher number of retrieved oocytes and an increased implantation rate [5]. These encouraging findings, however, were not reproduced by a later, doubleblinded randomized control study, where letrozole was added to a standard GnRH-antagonist protocol, at a dose and timing similar to the previous study presented [6]. Additional retrospective studies demonstrated that cotreatment with 5 mg letrozole resulted in reduction of gonadotropins dosage [13][14][15], while decreasing cancellation rates [13] and increasing pregnancy and live birth rates [14].…”
Section: Discussionmentioning
confidence: 81%
“…Several studies evaluated the co-administration of Letrozole during ovarian stimulation in patients suffering from diminished ovarian reserve, yielding conflicting results [4][5][6] . In these studies, Letrozole was started either concomitantly with or prior to gonadotropins, and was given for a total of 5 stimulation days.…”
Section: Introductionmentioning
confidence: 99%